2020
DOI: 10.13057/biodiv/d211113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ship-breaking activities on the abundance and diversity of macrobenthos in Sitakundu Coast, Bangladesh

Abstract: Abstract. Lipi JA, Noman MDA, Hossain MB, Abu Hena MK, Idris MH. 2020. Effects of ship-breaking activities on the abundance and diversity of macrobenthos in Sitakundu Coast, Bangladesh. Biodiversitas 21: 5085-5093. To articulate the ecological processes or anthropogenic impacts, it is necessary to explore various distributional patterns of benthic communities. The study was conducted to investigate the variability of macrobenthos between a ship braking and non-ship-breaking area along the Sitakunda coast, Chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The capetillids (especially Capitella capitate) are well known positive indicator groups which were not found in our study region. Besides, along this coastline, a recent study of Hossain et al (2020) found the negative indicator taxa Nerididae and Nephtyide had higher abundance in the unpolluted site than the reference site. Similarly, in our study Nerididae and Nephtyide were the most dominant taxa that may denote the non-polluted environment.…”
Section: Pollution Indicator Groupsmentioning
confidence: 81%
See 1 more Smart Citation
“…The capetillids (especially Capitella capitate) are well known positive indicator groups which were not found in our study region. Besides, along this coastline, a recent study of Hossain et al (2020) found the negative indicator taxa Nerididae and Nephtyide had higher abundance in the unpolluted site than the reference site. Similarly, in our study Nerididae and Nephtyide were the most dominant taxa that may denote the non-polluted environment.…”
Section: Pollution Indicator Groupsmentioning
confidence: 81%
“…The Polychaeta community is generally being used for the status of the benthic environment (Dean 2008;Hossain et al 2020). Among them, the presence of positive indicator group denotes the poor environmental condition and the absence of negative indicator groups prevail the detrimental environmental (Belan et al 2013;Hossain et al 2020). The capetillids (especially Capitella capitate) are well known positive indicator groups which were not found in our study region.…”
Section: Pollution Indicator Groupsmentioning
confidence: 99%